(untitled) (Journal of Educational Sciences, 2016)
In the article, the authors examine the characteristics of professional deformation of rural teachers. The specificity of pedagogical activity of the teacher assumes constant communication, which requires emotional interaction with students, parents and colleagues. In the professional activity of the teacher also focuses on the management of mental development of the individual student and the successful implementation of this task depends on the teacher who is able to consciously regulate emotional state: kindness, openness, trust with students, monitor their actions and deeds. The article discusses the views of modern scholars on the professional deformation of teachers. They all emphasize the difficulties and complexities of the teaching profession, which ultimately can lead to burnout, professional deformation. In conclusion, the authors emphasize those not all rural teachers knowledgeable in matters relating to professional deformation of teachers and its prevention.